2019
DOI: 10.3390/pharmaceutics11040175
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Release of a Non-Interacting Low Solubility Drug from Chitosan Pellets Using Different Pellet Size, Composition and Numerical Optimization

Abstract: Two size classes of piroxicam (PXC) pellets (mini (380–550 μm) and conventional (700–1200 μm)) were prepared using extrusion/spheronization and medium viscosity chitosan (CHS). Mixture experimental design and numerical optimization were applied to distinguish formulations producing high sphericity pellets with fast or extended release. High CHS content required greater wetting liquid volume for pellet formation and the diameter decreased linearly with volume. Sphericity increased with CHS for low-to-medium dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…The drug release data were described using the Weibull equation (Equation (6)) [ 25 , 26 ]. It distinguishes drug release mechanisms, which in the present work is very likely due to the different release characteristics of HPMC and HPC tablets [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The drug release data were described using the Weibull equation (Equation (6)) [ 25 , 26 ]. It distinguishes drug release mechanisms, which in the present work is very likely due to the different release characteristics of HPMC and HPC tablets [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…The consumed quantities of binder/gram solids for the MCC/PCT mixtures were between 4.8 and 17.6 mL, for the MCC/CPH between 7.2 and 18.4 mL, and for the MCC/BSF between 5.4 and 18.5 mL. The wet mass was immediately transferred into a spheronizer (Model 120, Caleva) fitted with a cross-hatch plate and rotated for 10 min, with the small pellets at 940 rpm corresponding to a linear velocity of 5.92 m/s and the large pellets at 1440 rpm corresponding to a linear velocity of 9.07 m/s [9]. MCC/modifier pellets with different proportions, 10% to 80%, were prepared and different density ranges were obtained.…”
Section: Preparation Of Pelletsmentioning
confidence: 99%
“…The obtained p app ranges were: 1.34-1.68 g/cc for MCC/PCT, 1.68-2.89 g/cc for MCC/CPH, and 1.68-4.68 g/cc for MCC/BSF. The two lines in each subfigure correspond to the experimental or "apparent" (solid symbols) and to the theoretical pellet densities, calculated from those of the primary components (for MCC 1.682 g/cc, for PCT 1.343, for CPH 2.893, and for BSF 4.675 g/cc) using Equation (9).…”
Section: Selection Of "Apparent" Density Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intelligent polymeric devices able to undergo morphological modifications in response to an internal or external stimulus, such as pH, redox balance, temperature, magnetic field, and light have been actively pursued [8][9][10]. In particular, in this Special Issue, Partheniadis et al [11] synthesized pharmaceutical pellets [12] of different sizes, using an extrusion/spheronization technique, and medium viscosity chitosan for the pH-dependent delivery of piroxicam. The authors suggested that a remarkable reduction in pellet size influenced the release rate, avoiding the need to employ hydrophilic excipients such as lactose [13].…”
mentioning
confidence: 99%